Asymmetric bilayers mimicking membrane rafts prepared by lipid exchange: nanoscale characterization using AFM-Force spectroscopy - Vázquez, Romina Florencia (2021)
Sphingolipids-enriched rafts domains are proposed to occur in plasma membranes and to mediate important cellular functions. Notwithstanding, the asymmetric transbilayer distribution of phospholipids that exists in the membrane confers the two leaflets different potentials to form lateral domains as next to no sphingolipids are present in the inner leaflet. How the physical properties of one leaflet can influence the properties of the other and its importance on signal transduction across the membrane are questions still unresolved. In this work, we combined AFM imaging and Force spectroscopy measurements to assess domain formation and to study the nanomechanical properties of asymmetric supported lipid bilayers (SLBs) mimicking membrane rafts. Asymmetric SLBs were formed by incorporating N-palmitoyl-sphingomyelin (16:0SM) into the outer leaflet of preformed 1,2-Dioleoyl-sn-glycero-3-phosphocholine (DOPC)/Cholesterol SLBs through methyl-β-cyclodextrin– mediated lipid exchange. Lipid domains were detected after incorporation of 16:0SM though their phase state varied from gel to liquid ordered (Lo) phase if the procedure was performed at 24 or 37 °C, respectively. When comparing symmetric and asymmetric Lo domains, differences in size and morphology were observed, with asymmetric domains being smaller and more interconnected. Both types of Lo domains showed similar mechanical stability in terms of rupture forces and Young's moduli. Notably, force curves in asymmetric domains presented two rupture events that could be attributed to the sequential rupture of a liquid disordered (Ld) and a Lo phase. Interleaflet coupling in asymmetric Lo domains could also be inferred from those measurements. The experimental approach outlined here would significantly enhance the applicability of membrane models.